2018
DOI: 10.1016/j.ajog.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Raman spectroscopy for biochemical monitoring of the human cervix throughout pregnancy

Abstract: BACKGROUND The cervix must undergo significant biochemical remodeling to allow for successful parturition. This process is not fully understood, especially in instances of spontaneous preterm birth. In vivo Raman spectroscopy is an optical technique that can be used to investigate the biochemical composition of tissue longitudinally and non-invasively in human beings, and has been utilized to measure physiology and disease states in a variety of medical applications. OBJECTIVE The purpose of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 63 publications
1
29
0
2
Order By: Relevance
“…Another approach is to use Raman spectroscopy to monitor the biochemical makeup and molecule concentration based upon signal intensity of the cervix in vivo throughout pregnancy. In a recent longitudinal study of women during pregnancy, this approach proved useful to identify many peaks that reflected extracellular matrix proteins, actin, and blood in the cervix that change throughout pregnancy and postpartum (173). This approach has also been used to study changes in fatty acid lipids, proteins, and amino acids the cervix in mice during pregnancy (174), as well as water content in non-pregnant and mice at term (175).…”
Section: Prospects For Non-invasive Approaches To Assess Characteristmentioning
confidence: 99%
“…Another approach is to use Raman spectroscopy to monitor the biochemical makeup and molecule concentration based upon signal intensity of the cervix in vivo throughout pregnancy. In a recent longitudinal study of women during pregnancy, this approach proved useful to identify many peaks that reflected extracellular matrix proteins, actin, and blood in the cervix that change throughout pregnancy and postpartum (173). This approach has also been used to study changes in fatty acid lipids, proteins, and amino acids the cervix in mice during pregnancy (174), as well as water content in non-pregnant and mice at term (175).…”
Section: Prospects For Non-invasive Approaches To Assess Characteristmentioning
confidence: 99%
“…Previous Raman spectroscopy studies have shown that the fingerprint region is sensitive to changes in collagen and lipid content as well as vascularity of the cervix during pregnancy. 2,36 Though decreased amplitude of fingerprint peaks associated with collagen and protein content were observed in day 19 mice compared to nongravid, prior work has indicated that total collagen content of the cervix remains constant during the remodeling process. 29,61 This observed decrease is likely due to the increasing hydration of the cervix, which results in a net decrease in collagen concentration.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have used Raman spectroscopy in the fingerprint region to study changes to the pregnant cervix during parturition in a mouse model as well as in human patients. 3638 High wavenumber Raman spectroscopy using a fiber optic probe facilitates noninvasive assessment of in vivo cervical hydration state which, when paired with the biochemical specificity of the fingerprint region, is a powerful tool for studying cervical remodeling in the context of pregnancy and labor.…”
Section: Introductionmentioning
confidence: 99%
“…reported that targeted brain cancer tissue biopsy is possible using in vivo Raman spectroscopy 8 . Other applications, such as in vivo monitoring of human cervix throughout pregnancy and of glucose concentration in blood, also have been reported 9 , 10 . In ophthalmology, only resonant Raman spectroscopy has been used for in vivo imaging, because the laser intensity needs to meet the safety criteria for eye evaluation 11 .…”
Section: Introductionmentioning
confidence: 99%